Nutrient and suspended solids removal from petrochemical wastewater via microalgal biofilm cultivation. (May 2017) - Hodges, Alan; Fica, Zachary; Wanlass, Jordan; VanDarlin, Jessica; Sims, Ronald
Abstract: Wastewater derived from petroleum refining currently accounts for 33.6 million barrels per day globally. Few wastewater treatment strategies exist to produce value-added products from petroleum refining wastewater. In this study, mixed culture microalgal biofilm-based treatment of petroleum refining wastewater using rotating algae biofilm reactors (RABRs) was compared with suspended-growth open pond lagoon reactors for removal of nutrients and suspended solids. Triplicate reactors were operated for 12 weeks and were continuously fed with petroleum refining wastewater. Effluent wastewater was monitored for nitrogen, phosphorus, total suspended solids (TSS), and chemical oxygen demand (COD). RABR treatment demonstrated a statistically significant increase in removal of nutrients and suspended solids, and increase in biomass productivity, compared to the open pond lagoon treatment. These trends translate to a greater potential for the production of biomass-based fuels, feed, and fertilizer as value-added products. This study is the first demonstration of the cultivation of mixed culture biofilm microalgae on petroleum refining wastewater for the dual purposes of treatment and biomass production. Highlights: Petroleum refining wastewater provided a suitable medium for biofilm microalgae. Biofilm microalgae removed significantly more nutrients than suspended microalgae. Biofilm microalgae removed significantly more solids than suspended microalgae. Microalgal biomass productivity was 10X greater in biofilm vs suspended growth.